Design and implementation of a 2 μA temperature-compensated MEMS-based real-time clock with ±4 ppm timekeeping accuracy. (April 2017) - Gronicz, Jakub; Pulkkinen, Mika; Yücetaş, Mikail; Halonen, Kari
Abstract: This paper presents the design and measurements of a temperature-compensated real-time clock based on a silicon resonator. The system exhibits timekeeping accuracy of ±4 ppm over the −40 to 85 °C temperature range. The current implementation is based on a TIA-based oscillator with a 27 kHz MEMS resonator, a differential PTAT temperature sensor and a 2nd order Σ Δ ADC. The temperature compensation is performed by an on-chip DSP block. The system consumes 2 μA of current and operates at 1.8 V nominal supply. The resonator operates off a 1.2 V DC bias without the need for a charge-pump or providing an external higher DC voltage. The integrated electronics interface has been implemented using a standard 0.18 μm CMOS process.